Occipital Condyle Fracture: A Case Report of a Typically Stable Fracture That Required Surgical Treatment - Takeshi Suzuki; Satoshi Maki; Masaaki Aramomi; Tomonori Yamauchi; Manato Horii; Koui Kawamura; Hiroshi Sugiyama; Seiji Ohtori (Case Reports in Orthopedics)
An occipital condyle fracture (OCF) is a relatively rare trauma that is now increasingly diagnosed because of the wide availability of computed tomography. For nondisplaced OCFs, conservative treatment is generally recommended, and there is no previous report of a nondisplaced OCF requiring surgery. We report a patient who had a nondisplaced OCF with craniocervical misalignment (a condyle-C1 interval > 2.0 mm) and C1-C2 translation treated with a halo vest and occipitocervical fusion surgery. An 87-year-old Asian woman fell from a 4-meter height and hit her head. She was transferred to our emergency room. Computed tomography revealed a nondisplaced impaction OCF with a 2.5 mm occipital condyle-C1 interval and a 5 mm C1-C2 translation. The fracture pattern was considered stable. However, since craniocervical misalignment and C1-C2 translation were present, the patient was placed in a halo device, and we reduced the occipitoatlantoaxial joint, adjusting the halo ring position preoperatively. Confirming reduction of the atlantooccipital facet joint and the atlantoaxial joint by computed tomography, we performed an occipitocervical fusion. This is the first report of a nondisplaced OCF with craniocervical misalignment and C1-C2 translation that required surgical treatment. Clinicians should be aware of craniocervical misalignment and atlantoaxial instability even in Tuli type 1 OCFs.